Bevlogen theologen: Over 150 jaar theologisch gemotiveerde vernieuwing van de samenleving - Dane, Harm G. (Religie & Samenleving, 2013)
In 2012 a book was published with portraits of fifteen Dutch protestant theologians living and working in the nineteenth and twentieth century, all very much involved in social and political activities, but greatly differing in theological en political positions. Each person portrayed offers in its own an impressive example of engagement and personal efforts for political justice or social welfare, but missing a conceptual framework to compare their efforts the portraits remain single pictures from the last two centuries. In this article a typology is used offered by Dietrich Bonhoeffer to investigate the possibility to interpret the social interventions of the different theologians in a more systematic way. The result is that we can distinguish three types of social intervention: social development work, educational work, and advocacy. It is remarkable that social movements pleading for personal development and individual growth do not find support among these protestant theologians.